A case of multiorgan IgG4-related disease with coronary artery vasculitis: Review of the 2019 Rheumatologic Classification Guidelines and what radiologists need to know - Jasmine Zhao, MD; Asmar Ghani, MD; Ali Mohammadzadeh, MD; Cato Chan, MD; James Shi, MD (Radiology Case Reports)
Immunoglobulin G4-related disease (IgG4-RD) is a rare fibroinflammatory disorder with diverse manifestations that can affect nearly any organ system. This case report describes a 58-year-old man presenting with obstructive jaundice due to a biliary stricture concerning for cholangiocarcinoma; however, eventual pathology, serology and imaging findings confirmed IgG4-RD. Over 2 years, the disease progressed to involve multiple organs, including 3-vessel coronary arteritis, a serious but underrecognized manifestation that may present with the ``pigs-in-a-blanket” sign on imaging. Despite treatment, the patient ultimately suffered a fatal cardiac event soon after. This case underscores the importance of recognizing characteristic imaging features, particularly those outlined in the 2019 American College of Rheumatology/European League Against Rheumatism classification criteria, which can act as a framework for radiologists and clinicians in early diagnosis. Prompt recognition, multidisciplinary collaboration, and timely treatment are essential to avoid unnecessary surgical interventions and reduce the risk of life-threatening complications.